Strategies for Islamic Financial Management at Educational Institution: Taskah Al-Fikh Orchard, Ayer Tawar, Penang, Malaysia - Kabeakan, Jesica; Hasanah, Uswah (Journal of English Language and Education, 2025)
This study to analyze the sharia financial management strategies applied at Taskah Al-Fikh Orchrad Ayer Tawar Penang Malaysia. Management in accordance with sharia principles is very important in every financial activity carried out by the institution. This study uses a qualitative approach with in-depth interviews with managers and analysis of relevant documents. The results of the study show that the strategies implemented include sharia based budget planning, zakat fund management, and strict transaction supervision. Overall, the management, and strict transaction supervision. Overall, the management of sharia law at Taskah Al-Fikh orchard has succeeded in maintaining smooth perations and compliance with sharia law, although there are still challenges faced and need to be improved.